HUBUNGAN KREDIBILITAS BOYGROUP "STRAY KIDS" SEBAGAI BRAND AMBASSADOR NACIFIC TERHADAP PERILAKU KONSUMTIF (SURVEI TERHADAP FOLLOWERS @NACIFICOFFICIAL.ID DI MEDIA SOSIAL INSTAGRAM) - Firdayanti (2023)
Many cosmetic brands choose Korean celebrities as their Brand Ambassadors. Celebrities are considered to have great influence among fans and the general public. The involvement of Korean celebrities in the promotion of cosmetic brands can also increase the sales and popularity of these brands. So Nacific chose Stray Kids as Brand Ambassador to increase consumer buying interest in Nacific products. This study aims to examine the relationship between Stray Kids as Nacific's Brand Ambassador towards the consumptive behavior of followers of the Instagram account @nacificofficial.id. This study uses the Source Credibility Theory proposed by Hovland, Janis, and Kelley with three factors namely expertise, trustworthiness, and attractiveness. The research method used is explanatory quantitative using primary data sources from questionnaires and secondary data from books, journals, articles, results of previous studies, and relevant websites. The sampling technique was carried out by using a random sampling technique. This study uses five stages of data analysis which include validity test, reliability test, correlation coefficient test, and significance test (T-test). The results of this study indicate that there is a significant relationship between Variable X (Brand Ambassador Credibility) and Variable Y (Consumptive Behavior) with a fairly strong correlation level. The T-test results show a t-count value of 6,203 so it can be concluded that there is a significant relationship between the credibility of Stray Kids as Nacific's Brand Ambassador and the consumptive behavior of followers of the Instagram account @nacificoffcial.id.